2016
DOI: 10.1111/bjep.12109
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood profiles of sleep problems and self‐regulation predict later school adjustment

Abstract: Early childhood profiles of self-regulation that include sleep problems offer a way to identify children at risk of poor school adjustment. Children with escalating early childhood sleep problems should be considered an important target group for school transition interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 102 publications
6
59
1
Order By: Relevance
“…In view of the fact that self‐regulation is defined as one of the main dimensions of temperament (Calkins & Degnan, ; Eisenberg, ; Kochanska, Murray, & Harlan, ; Posner & Rothbarth, ; Rothbarth & Gartstein, ), this premise can also be supported by a large number of studies showing the direct or indirect links of temperament with sleep problems in infancy and early childhood (Reid et al, ; Sadeh, ; Scher et al, ; Troxel et al, ). Also, recent studies of Williams et al (, 2017) highlight the developmental relatedness of sleep problems and self‐regulation in early childhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the fact that self‐regulation is defined as one of the main dimensions of temperament (Calkins & Degnan, ; Eisenberg, ; Kochanska, Murray, & Harlan, ; Posner & Rothbarth, ; Rothbarth & Gartstein, ), this premise can also be supported by a large number of studies showing the direct or indirect links of temperament with sleep problems in infancy and early childhood (Reid et al, ; Sadeh, ; Scher et al, ; Troxel et al, ). Also, recent studies of Williams et al (, 2017) highlight the developmental relatedness of sleep problems and self‐regulation in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, a range of regulatory processes is quickly developing at this age, and the main self‐regulatory skills are acquired by the end of preschool age (Bronson, ; Kopp, , ; Rothbarth, Sheese, Rueda, & Posner, ; Staples et al, ). As self‐regulation is considered to be a central factor in children's sleep (Papoušek, ; Williams, Nicholson, Walker, & Berthelsen, ), there is a necessity for a profound analysis of developmental changes in both sleep and self‐regulation in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Early childhood behavioral sleep problems have been linked with poorer attentional regulation (Williams and Sciberras, 2016; Williams et al, 2017) and executive function development over time (Bernier et al, 2013); and also poorer academic functioning (Quach et al, 2009). A recent analysis found that at 4–5 years, children with unresolved behavioral sleep problems, combined with above average levels of emotional dysregulation and poor attention were at higher risk for poor school adjustment (Williams et al, 2016a). Taken together, these findings suggest a link between these early problem behaviors and self-regulation and executive function development over time.…”
Section: Introductionmentioning
confidence: 99%
“…49 In a longitudinal study of children’s sleep habits and developmental outcomes, children with ongoing sleep problems in childhood were rated by teachers as more hyperactive, emotionally unsettled and disorganised, and as having poorer social skills 2–3 years later, suggesting that sleep problems influence brain development over time in a manner that interferes with self-regulation skills and broadly impacts wellbeing. 47, 48 Questions regarding sleep, affect, pain and functional outcomes therefore have developmental considerations, and the sleep-sensitive nature of children’s developing regulatory capacities suggests that affect may play an even more profound role in the sleep-pain relationship in children than in adults.…”
mentioning
confidence: 99%